(untitled) (Research, Society and Development, 2021)
Hypercaloric and hyperlipidic diets are often used in obesity research to induce excess weight and dyslipidemia in rats. In this experiment, Sprague-Dawley rats received a hypercaloric diet that was enriched with hydrogenated vegetable fat and sugar but hypoproteic and nutrient deficient. The rats’ body development and serum parameters were evaluated. Nine rats were fed a standard diet, while 27 rats were fed a hypercaloric diet prepared by substituting 15% of the standard diet with hydrogenated vegetable fat and 10% with sugar. Feed and water were provided ad libitum for 63 days. Between 35 and 98 days of age, the rats’ naso-anal length, body weight, and Lee index were measured weekly. At the end of the experimental period, blood samples were obtained to determine the serum levels of total cholesterol, triacylglycerol, and glucose. It was observed that the rats fed the hypercaloric diet containing hydrogenated vegetable fat and sugar exhibited less body development and did not develop either dyslipidemia or obesity although they exhibited increased serum glucose concentration.